ANALYSIS OF RISK FACTORS ASSOCIATED WITH THE INCIDENT OF DIPHTHERIA: STUDY OF DIPHTHERIA OUTBREAK IN THE WORKING AREA OF THE KENALI INPATIENT HEALTH CENTER, WEST LAMPUNG DISTRICT 2023 - Sendra Okta Fernando; Dian Isti Angraini; Jhons Fatriyadi Suwandi (Majalah Kedokteran Sriwijaya, 2024)
Diphtheria is an infectious disease that attacks the upper respiratory tract caused by the bacteria Corynebacterium diphtheriae. An area is declared a Diphtheria Outbreak if at least one Diphtheria Suspect is found. Lampung Province is one of the provinces that has experienced extraordinary cases of diphtheria. The number of diphtheria cases in Lampung Province in 2023 was 23 cases. West Lampung was declared a different KLB in 2023 with one person dying. Different transmissions are caused by several factors, namely host, agent and environment. This research aims to determine the relationship between host and environmental factors with different events in West Lampung. This research is an analytical observational study with a case-control approach. This research was carried out from April 2024 to August 2024. The sample in this study was 44, consisting of 11 case samples and 33 control samples. Data analysis used chi-square analysis. The results of this study indicate a relationship between host factors (contact history P-value 0.000 <0.05 OR 72.5 and knowledge P-value 0.030 < 0.05 OR 6.4). Environmental factors (house ventilation P-value 0.031 <α : 0.05 OR 6.2, house floor P-value 0.037 <0.05 OR 6.9 house lighting P-value 0.028 <0.05 OR 5 .5). With different incidents in the working area of the Kenali Inpatient Health Center, West Lampung Regency.